Dysregulation of Vesicular Glutamate Transporter VGluT2 via BDNF/TrkB Pathway Contributes to Morphine Tolerance in Mice - He, Liqiong; Xu, Wei; Zhang, Chengliang; Ding, Zhuofeng; Guo, Qulian; Zou, Wangyuan; Wang, Jian (Frontiers in Pharmacology, 2022)
Morphine is widely used in the treatment of moderate to severe pain. Long-term use of morphine leads to various adverse effects, such as tolerance and hyperalgesia. Vesicular glutamate transporter 2 (VGluT2) accumulates glutamate into synaptic vesicles and plays multiple roles in the central nervous system. However, the specific role of VGluT2 in morphine tolerance has not been fully elucidated. Here, we investigated the regulatory role of VGluT2 in morphine tolerance and assessed the potential role of the brain-derived neurotrophic factor (BDNF)/ tyrosine kinase B (TrkB) pathway in VGluT2 mediated morphine antinociceptive tolerance in mice. In the present study, we found that VGluT2 is upregulated in the spinal cord after the development of morphine tolerance. Furthermore, inhibition of VGluT2 with its antagonist (Chicago sky blue 6 B, CSB6B) or knockdown of VGluT2 by lentivirus restored the analgesic effect of morphine, suppressed the activation of astrocytes and microglia, and decreased glial-derived pro-inflammatory cytokines. Overexpression of VGluT2 by lentivirus facilitated morphine tolerance and mechanical hyperalgesia. In addition, we found the expression of BDNF is correlated with VGluT2 expression in the spinal cord after chronic morphine administration. Intrathecal injection of the BDNF/ TrkB pathway antagonist K252a attenuated the development of morphine tolerance and decreased the expression of VGluT2 in the spinal cord, which suggested the BDNF/TrkB pathway participates in the regulation of VGluT2 in morphine tolerance. This study elucidates the functional capability of VGluT2 in modulating morphine tolerance and identifies a novel mechanism and promising therapeutic target for morphine tolerance.